(untitled) (Impact: Journal of Transformation, 2019)
This study involved an investigation into the factors contributing to a high rate of illiteracy among the Borana Muslim women in Mata’arba location in Marsabit County. The factors investigated included cultural and other general factors that affect formal education among the Borana Muslim girls in marginalized areas. These factors include early marriage, ethnic conflicts, pastoralism, poverty, preferential education for boys rather than girls, female genital mutilation (FGM), HIV and AIDS. The study adopted a qualitative method, and was guided by phenomenological research design in collecting data. Structured interview questions and participant observation tools were used in answering the research questions. The research population was composed of Borana Muslim women aged 12 to 40 years who have never had an opportunity to go to school. The interview questions were translated into the language of the respondents and then administered directly to the sampled respondents through the help of a research assistant and the resultant data analysed. The study showed that the attitude of Borana Muslim women towards formal education is generally positive: They viewed illiteracy among the girls as a critical issue. Nevertheless, to ensure equitable quality education for the women, a form of intervention is urgently needed. In conclusion, the study observed that there is a need for all stakeholders to step up the action concerning the importance of formal education among girls. This calls for a joint effort by the government, the community and the Borana women themselves to arise and fight illiteracy at all costs. Key highlights on how to improve the Borana Muslim women’s situation were raised. They include; creating awareness on the integral dimension in inclusivity of Borana girls in education, discouraging early marriages, provision of mobile formal schools among the pastoralist communities, and enhancing security among the communities. The recommendations strive to form a basis for serious consideration by anyone wishing to promote lifelong education and eradicate illiteracy among the Borana Muslim girls in marginalized areas.